Co‐encapsulation of lupulon and xanthohumol in lecithin‐based nanoliposomes developed by sonication method. Issue 9 (30th June 2019) - Khatib, Neda; Varidi, Mohammad Javad; Mohebbi, Mohebbat; Varidi, Mehdi; Hosseini, Seyed Mohammad Hashem
Abstract: Co‐encapsulation of lupulon and xanthohumol, as major bioactive components of hop in lecithin‐based nanoliposomes was developed by sonication method. The procedure of production was optimized by considering the duration and the power of ultrasound device as well as the concentration of lecithin as variables for the Response Surface Methodology. The average particle size, ζ‐potential, and the melting point of nanoliposomes were determined to be 167.2 nm, 36.4 mV, and 123.19°C, respectively. Encapsulation efficiency (EE%) of lupulon was 71.12%, while for xanthohumol it was 67.81%. Transmission Electron Microscopy confirmed the formation of nanoscale‐liposomes. The IC50 indicating the antioxidant activity of xanthohumol/lupulon‐loaded nanoliposomes was found to be 60.38 µg/ml. The minimum inhibitory concentration against Clostridium perfringens was equal to 32 mg/ml. This study shows the capability of lupulon and xanthohumol as nature products that simultaneously encapsulated in a liposomal coating to replace synthetic additives in model food such as meat products. Practical applications: The global consumer trends to avoid synthetic additives in food products have been progressively increased in recent years. Lupulon and xanthohumol are two major components of hop extract which possess a number of promising biological activities. However, due to their bitter taste and strong flavor, these are not commercially used in food products in free state. In this study, lupulon and xanthohumol were simultaneously encapsulated in lecithin‐based nanoliposome by employing the sonication method. The procedure of nanoliposome production was optimized based on the efficiency of encapsulated materials released from the encapsulants. The biological activities of the lupulon/xanthohumol nanoliposomes were evaluated. The promising results from this study suggested replacing of synthetic additives in real food systems such as meat products by these native components in the format of encapsulation.